Doctors as health managers: an oxymoron, or a good idea? - Erwin Loh (Journal of Work-Applied Management, 2015)
Purpose - The purpose of this paper is to review the current literature and summarises the benefits and limitations of having doctors in health management roles in today’s complex health environment. Design/methodology/approach - This paper reviews the current literature on this topic. Findings - Hospitals have evolved from being professional bureaucracies to being managed professional business with clinical directorates in place that are medically led. Research limitations/implications - Limitations include the difficulty doctors have balancing clinical duties and management, restricted profession-specific view and the lack of management competencies and/or training. Practical implications - The benefits of having doctors in health management include bottom-up leadership, specialised knowledge of the profession, expert knowledge of clinical care, greater political influence, effective change champions to have on-side, frontline leadership and management, improved communication between doctors and senior management, advocacy for patient safety and quality, greater credibility with public and peers and the perception that doctors have more power and influence compared to other health professionals can be leveraged. Originality/value - Overall, there are more benefits than there are limitations to having doctors in health management but there is a need for more management training for doctors.